Exploring the determinants of fundraisers' voluntary information disclosure on crowdfunding platforms: A risk-perception perspective. Issue 3 (11th June 2018) - Wang, Tao; Liu, Xiaowei; Kang, Minghui; Zheng, Haichao
Abstract : Purpose: The purpose of this paper is to examine factors affecting fundraisers' voluntary information disclosure on crowdfunding platforms based on risk-perception theory (RPT). Design/methodology/approach: Structural equation modeling was employed to test the hypothesized relationships using data collected from China. Findings: The authors found that plagiarism risk and financing risk are two important variables that influence fundraisers' voluntary information disclosure. Specifically, plagiarism risk has a negative effect on fundraisers' voluntary information disclosure, while financing risk has a positive effect on fundraisers' voluntary information disclosure. Plagiarism risk is affected by information concerns, perceived control, project innovativeness, and quality of alternatives, while financing risk is affected by protection policy and information norms. Originality/value: This study enriches crowdfunding research by identifying factors influencing fundraisers' voluntary information disclosure and contributes to RPT by applying it in a new crowdfunding context.